Blind spots on the Magic Mountain: Zofia Nałkowska's Choucas (1926) - Watroba, K (Modern Humanities Research Association and the School of Slavonic and East European Studies, University College London, 2021)
Zofia Nałkowska's little-known Polish novel Choucas (1926), recently translated into English for the first time by Ursula Phillips, has often been compared to Thomas Mann's famous German novel, The Magic Mountain (1924), with critics referring to Choucas as a ‘miniature’ of The Magic Mountain. This article offers the first comprehensive comparative reading of the two novels with the aim of showing exactly how they relate to each other, as well as finding a more productive way of handling literary pairings like this one — where the difference in status and cultural pull is so vast as to seem unbridgeable.